Thermodynamic reasons of agglomeration of dust particles in the thermal dusty plasma - Vishnyakov, V.I.; Dragan, G.S. (Condensed Matter Physics, 2003)
The thermodynamic equilibrium of thermal dusty plasmas consisting of
ionized gas (plasma) and solid particles (dust grains), which interact with
each other, is studied. The tendency of grains in dusty plasmas to agglomerate
corresponds to the tendency of dusty plasmas to balanced states.
When grains agglomerate, electrical perturbations generated by each grain
concentrate inside the agglomerate. The plasma is perturbed only by the
agglomerate’s exterior surface. The greater number of possible states for
electrons and ions in plasma depends on the volume of perturbation of
grains. The fewer are the perturbations the greater is the amount of possible
states for electrons and ions in plasma. If the grains collected from a
distance smaller than 8 Debye lengths, the total volume of perturbations is
minimized; the free energy of the plasma is also minimized. Вивчається термодинамічна рівновага в термічній запорошеній
плазмі, яка містить іонізований газ і тверді частинки (пилинки), що
взаємодіють між собою. Тенденція пилинок в запорошеній плазмі до
агломерації відповідає тенденції запорошеної плазми до збалансованих станів. У випадку агломерації електричні збурення, породжені кожною пилинкою, зосереджуються всередині агломерату. Тому
збурення в плазмі викликані лише зовнішньою поверхнею агломерату. Більшість можливих станів електронів та іонів у плазмі залежить
від об’єму, зайнятого пилинками: чим менше збурень, тим більше в
плазмі станів, доступних для іонів та електронів. Якщо пилинки зближуються до відстані менше восьми дебаєвських радіусів екранування, сумарний об’єм збурень і вільна енергія плазми мінімізуються.